Otatea ramirezii (Poaceae: Bambusoideae: Bambuseae) flower description and the importance of the Mexican national living bamboo collection - Ruiz-Sanchez, Eduardo (Phytotaxa, 2013)
Botanical gardens have several aims, among which is to increase awareness of plant diversity, to study it, and to conserve it. The Francisco Javier Clavijero Botanical Garden at the Instituto de Ecología, in Xalapa, Mexico, curates the Mexican national living national bamboo collection. In 2010 a new Otatea species was collected, described and cultivated in the living bamboo collection. Two years after being planted, this bamboo began to flower in the summer of 2012. I decided to visit the type locality and I found the entire population flowering. Based on collected specimens, the synflorescences and spikelets of Otatea ramirezii are described and these structures are compared with those of the known Otatea species described with flowers. The living national bamboo collection of Mexico is important for the preservation of native species and, given that the flowering cycles of most bamboo species are not known, for the documentation of their life cycles.